The design and development of study materials to facilitate skills development in recognising statements in academic text - Kuboni, Olabisi (My University, 2015)
This paper outlines the strategies employed in the design and development of study materials for building learner competence in recognizing and differentiating among statements in academic text. This specific skill represents one aspect of the broader capability of unpacking complex academic information, which appears to be a challenge for a growing number of higher education students, in particular those belonging to the mature cohort. Drawing on prior knowledge from personal engagement with academic texts, the author developed a draft instructional framework around three statement-types, namely, facts, assertions, and generalizations. Based on feedback obtained from peer review of the draft framework, an in-depth analysis of the statement-types was conducted. This analysis entailed matching dictionary/thesaurus definitions of each of the three with relevant segments of text drawn from a selection of journals. This exercise led to a fuller conception of each statement-type and the development of a more fleshed out instructional framework. The first of the three statement-types was also changed from "facts" to "facts and factual information." This fleshed-out framework provided the basis for the development of the study materials, which comprise a series of slide (PowerPoint)-sound presentations with accompanying assessment exercises, and which are organized within an online study environment. Issues receiving special attention in the paper include cognitive task analysis as an alternative instructional design strategy when the focus is on building schemata, as well as the pros and cons of utilizing embedded versus generic materials for skills training.
Paper presented at the Regional Conference on Institutionalising Best Practice in Higher Education, UWI, St. Augustine, Trinidad and Tobago, 24-26 June, 2015.
Keywords: Materials preparation; Teaching materials; Learning skills; Skill development; Adult learning; Adult students; Information literacy; Cognitive development